Africa: in search of security after the Cold War - Badmus, Isiaka Alani (Africana Studia, 2020)
In this paper, I explore the state of African security in the context of both the Cold War and post-Cold War periods. Then, I unmask the dangers inherent in the conceptualisation of security in the realist perspective. I contend that since African security quagmires are multifaceted, the realist thesis is misleading and fails to address the complex nature of African security, hence the need for rethinking African security. Since socio-economic insecurity is the continent’s bane to guarantee human security, I argue that non-military security issues/concerns should be the utmost priorities of African leaders. Doubtless, the birth of the AU, NEPAD, African Calabashes etc are commendable, but these efforts can only bear fruits if, and only if, there is strong political will and commitment on the part of African leadership and Africans in general. Keywords: Security in Africa; the OAU/AU; the UN; ECOWAS; NEPAD; Cold War; Post-Cold War; Collective Defence; African Calabashes.